The Effect of Competence, Motivation and Rewards on Employee Performance with Work Spirit as an Intervening Variable on Technical Service Employees of PT PLN (Persero) ULP Pangkalan Brandan - Endrawan Surbakti; Kiki Farida Ferine (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to explore the influence of competence, motivation, and rewards on employee performance, with work morale as a mediator among Technical Service Employees at PT PLN (Persero) ULP Pangkalan Brandan. Quantitative methods were used for this study, using a survey approach. A complete population of 52 employees was sampled using a census approach. Data collection involved questionnaires, which were then analyzed using Partial Least Squares (PLS) techniques. The results showed that competence significantly and positively influenced employee performance and work morale. Motivation was not found to significantly influence employee performance or work morale. Rewards had a significant effect on work morale but did not substantially affect employee performance. Furthermore, work morale positively and significantly influences employee performance. Analysis of the indirect effect showed that work morale did not mediate the relationship between competence and motivation related to employee performance, nor did it mediate the effect of rewards on employee performance. This study concluded that employee performance is primarily influenced by competence and work morale, not motivation and rewards.